Inverse Relationship Between Leydig Cell Density and Metastatic Potential of Prostatic Adenocarcinoma - W. John Wang; Y. Albert Yeh; Paul Stout; Kang Fan (Analytical Cellular Pathology)
Purpose: Evaluate the relationship between metastatic potential of prostatic adenocarcinoma (PC) and testicular Leydig cell density. Materials and methods: Tissue samples from 111 men, age 52–85, with PC and bilateral orchiectomy were evaluated for Leydig cell density. The patients were divided into two groups: Group A were patients with metastasis (n=36) and Group B were patients without metastasis (n=75). Leydig cell density was determined by direct manual microscopic cell count on the tissue sections. The means of cell counts by four pathologists, expressed as cell/0.78 mm2 were used for analysis. The normally distributed data were analyzed by two‐tail Student’s t‐test. Thirty‐eight age‐compatible autopsy cases who died of unrelated causes served as normal controls. Results: The mean of Leydig cell count in group A patients was 14.43 (14.43 ± 1.19 SE). Mean of Group B was 47.05 (47.05 ± 4.05 SE) whereas normal controls displayed a mean of 48.66 (48.66 ± 2.94 SE). Group A was significantly different from control (p<0.00001). Group A and Group B were also significant different (p<0.001) whereas control was not significantly different from Group B (p>0.75). Conclusions: Patients with metastatic adenocarcinoma of prostate, as a group, have a significantly lower Leydig cell density than patients without metastasis or patients without PC in compatible age groups. The hormonal relationship between this observation is however unknown. One possible explanation is that PC subpopulation with metastatic potential may require different level of endogenous androgen or are androgen‐independent.